2020
DOI: 10.3390/ijerph17239096
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Psychological Impact of COVID-19 among Healthcare Workers: A Meta-Analysis

Abstract: Previous meta-analyses were conducted during the initial phases of the COVID-19 pandemic, which utilized a smaller pool of data. The current meta-analysis aims to provide additional (and updated) evidence related to the psychological impact among healthcare workers. The search strategy was developed by a medical librarian and bibliographical databases, including Medline, Embase, CINAHL, PsycINFO, and Scopus were searched for studies examining the impact of the COVID-19 pandemic on the psychological health of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
299
10
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(350 citation statements)
references
References 96 publications
(215 reference statements)
30
299
10
11
Order By: Relevance
“…Another reason was that our sample population focused on HCWs from all sectors, while Lai et al employed a hospitalbased survey, which may involve higher risks for exposure to COVID-19 and thus could lead to increased fear of spreading the virus and being isolated (19). The prevalence was also much lower compared to that in USA of 60.2% (31). Although USA is a highincome country with advanced health care system, HCWs in this country still suffered from stress because of the overwhelming COVID-19 cases and deaths.…”
Section: Discussionmentioning
confidence: 97%
“…Another reason was that our sample population focused on HCWs from all sectors, while Lai et al employed a hospitalbased survey, which may involve higher risks for exposure to COVID-19 and thus could lead to increased fear of spreading the virus and being isolated (19). The prevalence was also much lower compared to that in USA of 60.2% (31). Although USA is a highincome country with advanced health care system, HCWs in this country still suffered from stress because of the overwhelming COVID-19 cases and deaths.…”
Section: Discussionmentioning
confidence: 97%
“…The respective scores for depression, anxiety, and stress were calculated by totaling the scores for the respective associated items, and the severity rating index was used to determine the respondent's status in each regard. The severity rating index for each DASS subscale as follow (depression was comprising normal (0-9), mild (10-13), moderate (14-20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28+). Anxiety scoring comprising normal (0-7), mild (8-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), extremely severe 20+.…”
Section: The Research Instrumentsmentioning
confidence: 99%
“…Anxiety scoring comprising normal (0-7), mild (8-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), extremely severe 20+. Stress scoring comprising normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), sever (26-33), extremely severe (34+). In the original study, the Cronbach's alpha values for depression, anxiety, and stress were 0.91, 0.84, and 90, respectively [30].…”
Section: The Research Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from rapid reviews and meta-analyses have shown that hospital staff members in contact with infected patients (“frontline hospital staff members”) appear to be at increased risk of reporting symptoms of exhaustion, depression, anxiety [ 5 ], short- and long-term mental health problems [ 6 ], acute and post-traumatic stress [ 7 , 8 , 9 ], and psychological distress [ 5 , 10 ]. Batra et al [ 11 ], in their meta-analysis, summarized results from 65 studies, including 79,437 hospital staff members, and they reported the following prevalence rates: anxiety: 34.4%; depression: 31.8%; stress: 40.3%; post-traumatic stress syndrome: 11.4%; insomnia: 27.8%; psychological distress: 46.1%, and burnout: 37.4%. The following specific risk factors were identified: lower age, being more junior, being the parents of young children, having an infected family member, lack of practical support, stigma [ 5 , 7 ], heavy workload, lack of training, lack of social support, and limited work experience [ 7 ].…”
Section: Introductionmentioning
confidence: 99%